Recent advances in NIR-II fluorescence based theranostic approaches for glioma - Li, Jiaying; Ling, Jue; Yao, Chaoyi (Frontiers in Chemistry, 2022)
Glioma is one of the most common malignant tumors in central nervous system with deadly poor prognosis. However, the desirable treatment of gliomas still remains great challenges. The recent development of near infrared (NIR) II (1000-1700 nm) theranostic agents offers power strategies in diagnosis, targeting delivering drugs and accurate therapy. Benefiting from the strong capacity of NIR II light on deep tissue penetration, improved spatiotemporal resolution can be achieved to facilitate in vivo detection of gliomas using fluorescence imaging and realize high contrast fluorescence-guided surgery. Drug delivery nano-platform with NIR II agents can not only preciously visualize tumor but also monitor the delivery process in real-time. In addition, the combination of target drug delivery system and photodynamic therapy (PDT) and photothermal therapy (PTT) in NIR region significantly improves the therapeutic effect against gliomas. Thus this mini-review concludes the recent development of NIR-II fluorescence based theranostic agents in glioma.